PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PT SAKTI COAL JAYA DENGAN LINGKUNGAN KERJA SEBAGAI MEDIATOR - Hermawan, Eric; Arifin, Antoni Ludfi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study discusses the independent variables of the work environment which are used as mediators to determine the indirect influence of leadership and organizational culture on the performance of employees of PT. Sakti Coal Jaya. This study processed the questionnaire data as many as 50 respondents from the population of 85 employees of PT. Sakti Coal Jaya. The calculation of simple linear regression and multiple linear regression was determined after the research data met the validity, reliability, normality, multicollinearity and heteroscedasticity tests. The significance test for simple regression was carried out by t-test, by comparing tcount and ttable. The simple regression equation is significant and positive if tcount > ttable. Meanwhile, the significance test for multiple regression was carried out using the F-test, by comparing Fcount with Ftable. The multiple regression equation is significant and positive if Fcount>Ftable. The results obtained from this study, all effects, both direct and indirect, are significant and positive.